2015
DOI: 10.1088/0004-637x/809/1/90
|View full text |Cite
|
Sign up to set email alerts
|

Argo-Ybj Observation of the Large-Scale Cosmic Ray Anisotropy During the Solar Minimum Between Cycles 23 and 24

Abstract: This paper reports on the measurement of the large-scale anisotropy in the distribution of cosmic-ray arrival directions using the data collected by the air shower detector ARGO-YBJ from 2008 January to 2009 December, during the minimum of solar activity between cycles 23 and 24. In this period, more than 2 × 10 11 showers were recorded with energies between ∼1 and 30 TeV. The observed two-dimensional distribution of cosmic rays is characterized by two wide regions of excess and deficit, respectively, both of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 46 publications
(69 reference statements)
0
62
0
Order By: Relevance
“…Above the energy range where cosmic rays are directly affected by inner heliospheric processes (see, e.g., Florinski et al 2013;Manuel et al 2014;Florinski et al 2015), a statistically significant anisotropy has been observed by a variety of experiments, sensitive to different energy ranges (from tens of GeV to a few PeV), located on or below the Earth's surface in the northern hemisphere (Nagashima et al 1998;Hall et al 1999;Amenomori et al 2005Amenomori et al , 2006Guillian et al 2007;Abdo et al 2009;Aglietta et al 2009;Zhang et al 2009;Munakata et al 2010;Amenomori et al 2011;de Jong et al 2011;Cui et al 2011;Bartoli et al 2015) and in the southern hemisphere (Abbasi et al 2010a(Abbasi et al , 2011a(Abbasi et al , 2012bAartsen et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Above the energy range where cosmic rays are directly affected by inner heliospheric processes (see, e.g., Florinski et al 2013;Manuel et al 2014;Florinski et al 2015), a statistically significant anisotropy has been observed by a variety of experiments, sensitive to different energy ranges (from tens of GeV to a few PeV), located on or below the Earth's surface in the northern hemisphere (Nagashima et al 1998;Hall et al 1999;Amenomori et al 2005Amenomori et al , 2006Guillian et al 2007;Abdo et al 2009;Aglietta et al 2009;Zhang et al 2009;Munakata et al 2010;Amenomori et al 2011;de Jong et al 2011;Cui et al 2011;Bartoli et al 2015) and in the southern hemisphere (Abbasi et al 2010a(Abbasi et al , 2011a(Abbasi et al , 2012bAartsen et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…IVA and Table II). As known from literature [22,23], the deficit regions parallel to the excesses are due to using also the excess events to evaluate the background, which turns out to be overestimated. Symmetrically, deficit regions, if any, would be expected to be surrounded by weaker excess halos, which were not observed.…”
Section: Sidereal Anisotropymentioning
confidence: 90%
“…The p+He spectra by CREAM [14], ARGO-YBJ [6] and the hybrid experiment [20] below the knee, the spectra by Tibet AS [21] and KASCADE [22] above the knee are shown for comparison. In our result, the error bar is the statistical error, and the shaded area represents the systematic uncertainty [23] for details). In the last years many experiments presented an evidence of the existence of a medium angular scale anisotropy in both emispheres.…”
Section: Cosmic Ray Anisotropymentioning
confidence: 99%
“…From an observational point of view, a statistically significant anisotropy has been observed by a variety of experiments, sensitive to different energy ranges (from tens of GeV to a few PeV), located on or below the Earth's surface in the Northern Hemisphere (Nagashima et al 1998;Hall et al 1999;Amenomori et al 2005Amenomori et al , 2006Amenomori et al , 2011Guillian et al 2007;Abdo et al 2009;Aglietta et al 2009;Zhang et al 2009;Munakata et al 2010;Cui et al 2011;de Jong et al 2011;Bartoli et al 2015) and in the Southern Hemisphere (Abbasi et al 2010(Abbasi et al , 2011(Abbasi et al , 2012Aartsen et al 2013Aartsen et al , 2016.…”
Section: The Problem Of Anisotropies and Corresponding Approachesmentioning
confidence: 99%